2011
DOI: 10.1029/2010ja015642
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dynamic ionospheric outflow on the ring current

Abstract: [1] The importance of ionospheric O + on the development of the storm time ring current is recognized but not well understood. The addition of this outflow in global MHD models has the potential to change the magnetic field configuration, particle densities and temperatures, and the convection electric field. This makes including heavy ion outflow in ring current simulations difficult, as this addition cannot be easily decoupled from a host of other changes. This study attempts to overcome this problem by usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
75
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 67 publications
4
75
0
Order By: Relevance
“…Additionally, if MHD predictions of reduced CPCP values resulting from O + outflow are correct, the E × B drift of fresh plasma will be greatly diminished. Welling et al (2011) demonstrated that these two factors caused weak Earthward penetration of plasma into the ring current. Warmer populations, especially those entering duskward of local midnight, could gradient-curvature drift out of the code domain without being captured.…”
Section: Ring Currentmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, if MHD predictions of reduced CPCP values resulting from O + outflow are correct, the E × B drift of fresh plasma will be greatly diminished. Welling et al (2011) demonstrated that these two factors caused weak Earthward penetration of plasma into the ring current. Warmer populations, especially those entering duskward of local midnight, could gradient-curvature drift out of the code domain without being captured.…”
Section: Ring Currentmentioning
confidence: 99%
“…Though this result is likely an extreme case, it demonstrates how the effects of heavy ion outflow are complex and non-linear. Other, less critical plasma sheet characteristics, such as spatial asymmetries in density and composition, also contribute to these effects (Welling et al 2011), as discussed in Sect. 4.4.…”
Section: Ring Currentmentioning
confidence: 99%
See 2 more Smart Citations
“…This is the reason why coupled models are intensively developed and improved during recent years. Besides several cases considered here, the latest examples include: coupling between the RCM (ring current model) and Versatile Electron Radiation Belt (VERB) code (Subbotin et al, 2011); coupling between RAM-SCB code (ring current model) and BATSRUS/SWMF (MHD with the RCM) (Welling et al, 2011;Zaharia et al, 2010); coupling between two ring current models RAM and the RCM ; one way coupling between MHD Open Geospace General Circulation Model (Open GGCM) -the RCM (ring current model) (Hu et al, 2010). None of these models however is 'ideal' (including the examples presented in detail earlier) in the sense that all of them have some shortcuts.…”
Section: Discussion and Directions For Future Workmentioning
confidence: 99%